Dabigatran versus rivaroxaban for the prevention of stroke and systemic embolism in atrial fibrillation in Canada - Kansal, Anuraag R.; Sharma, Michael; Bradley-Kennedy, Carole; Clemens, Andreas; Monz, Brigitta U.; Peng, Siyang; Roskell, Neil; Sorensen, Sonja V. (Thrombosis and Haemostasis, 2012)
Canadian patients with atrial fibrillation (AF) in whom anticoagulation is appropriate have two new choices for anticoagulation for prevention of stroke and systemic embolism – dabigatran etexilate (dabigatran) and rivaroxaban. Based on the RE-LY and ROCKET AF trial results, we investigated the cost-effectiveness of dabigatran (twice daily dosing of 150 mg or 110 mg based on patient age) versus rivaroxaban from a Canadian payer perspective. A formal indirect treatment comparison (ITC) of dabigatran versus rivaroxaban was performed, using dabigatran clinical event rates from RE-LY for the safety-on-treatment population, adjusted to the ROCKET AF population. A previously described Markov model was modified to simulate anticoagulation treatment using ITC results as inputs. Model outputs included total costs, event rates, and quality-adjusted life-years (QALYs). The ITC found when compared to rivaroxaban, dabigatran had a lower risk of intracranial haemorrhage (ICH) (relative risk [RR] = 0.38; 95% confidence interval [CI] 0.21 –0.67) and stroke (RR = 0.62; 95%CI 0.45–0.87). Over a lifetime horizon, the model found dabigatran-treated patients experienced fewer ICHs (0.33 dabigatran vs. 0.71 rivaroxaban) and ischaemic strokes (3.40 vs. 3.96) per 100 patient-years, and accrued more QALYs (6.17 vs. 6.01). Dabigatran-treated patients had lower acute care and long-term follow-up costs per patient ($52,314 vs. $53,638) which more than offset differences in drug costs ($7,299 vs. $6,128). In probabilistic analysis, dabigatran had high probability of being the most cost-effective therapy at common thresholds of willingness-to-pay (93% at a $20,000/QALY threshold). This study found dabigatran is economically dominant versus rivaroxaban for prevention of stroke and systemic embolism among Canadian AF patients.
Keywords: Anticoagulation; atrial fibrillation; cost-effectiveness; dabigatran; rivaroxaban; RE-LY; ROCKET AF